Effects of the metabolic uncoupler TCS on residual sludge treatment: Analyses of the microbial community and sludge dewaterability potential. (February 2022) - Lin, Wei; Ding, An; Ngo, Huu Hao; Ren, Zixiao; Nan, Jun; Li, Guibai; Ma, Jun
Abstract: Residual sludge is a by-product with a large volume and complex composition from wastewater treatment plants. It is significant to reduce sludge volume to decrease the negative effects of sludge on environmental pollution and needless land use. We investigated the effects of uncoupler 3, 3′, 4′, 5-tetrachlorosalicylanilide (TCS) on the properties of sludge. After adding 0.12 g TCS/g VSS with 24 h mixing, the sludge concentration and total ATP content decreased by 51.1% and 60.8%, respectively. At the same time, the microbial community also changed significantly, leading to the decrease of richness and diversity. Additionally, the secretion of extracellular polymeric substances (EPS) reduced approximately 43% under the addition of 0.12 g/g VSS compared with the control. The decrement of EPS may be explained by the decreased relative abundance of functional bacteria (i.e. Chloroflexi reduced about 60% and Nitrospirota reduced about 31%). Notably, the addition of TCS before coagulation conditioning (FeCl3 ) promoted the adhesion of sludge flocs according to the theory of Extended Derjaguin Landau Verwey Overbee (XDLVO), leading to the increased hydrophobicity of the residual sludge. Therefore, energy uncoupling has the potential of improving sludge dewaterability. Graphical abstract: Image 1 Highlights: Effects of TCS on residual sludge's microbial community and reduction were explored. EPS secretion of functional bacteria in residual sludge decreased by adding TCS. XDLVO was used to evaluate the construction of sludge floc during energy uncoupling. TCS exhibited a great potential to improve sludge dewaterability.